The Modified Strain Index: A Composite Measure of Injury Risk for Signers. Issue 4 (14th May 2021) - Roman, Gretchen; Peterson, Daniel S.; Ofori, Edward; Vidt, Meghan E.
Abstract: Up to 81% of individuals who are fluent in sign language (signers) report pain. Non-native signers (with non-signing, non-deaf parents) report greater pain than natives (≥1 signing, deaf parent). The goal of this study was to develop a composite measure of injury risk (the modified Strain Index for signers) based on previously identified biomechanics unique to signers and examine scores across sub-groups of natives and non-natives. Non-natives were hypothesized to have greater pain and higher composite scores than natives. Ten natives and 15 non-natives used a numeric scale to rate pain while signing. Measures included 'micro' rests, muscle activation, ballistic signing, non-neutral joint angle, and work envelope. Descriptive statistics were used to create categorical ratings and backward elimination multiple linear regression to establish rank order of the biomechanical tasks. Participant performance was rated, and the product of the multipliers across tasks created a score. Pain intensity was associated with the composite score (r = 0.46; p = 0.02), however there was no difference between natives (score = 13.39 ± 3.1) and non-natives (score = 19.55 ± 4.7; p = 0.34). This work presents an approach to incorporate multiple biomechanical factors into a single, composite measure unique to signers, however further evidence-based adjustments are needed to enhance its robustness.